Market Timing Abilities of Mutual Fund Managers – An Empirical Study - Damani, Akshay; Sethia, Muskaan; Mehta, Nivid (Indian Journal of Finance, 2024)
Purpose : The present study applied the unconditional Treynor–Mazuy (TM) and Henriksson–Merton (HM) models and evaluated the market timing abilities of 58 top 5-star rated funds from Australia for the period from July 31, 2019, to July 31, 2021, which has been considered as the pandemic period for the study, which enabled the investors to analyze and compare the market timing skills of fund managers for better investment decisions through the application of the market timing models. Methodology : For the selected fund’s net asset values (NAV), Australian 10-year bond yield and ASX index points were collated. Subsequently, the NAV returns were regressed against the market premium and quadratic factors (as independent variables) of the TM and Henrikson–Merton (HM) models, respectively. The coefficients of these independent variables were tested for their statistical significance. Based on the p-values and positive or negative values of these coefficients, the presence or absence of market timing abilities of fund managers was identified. Findings : The findings indicated the absence of market timing in most funds during the COVID-19 period based on the market timing models, which were developed by TM and HM models. Practical Implications : The study enabled investors to make a rational decision in regard to investing in mutual funds during abnormal times. It also provided insights to fund managers in regard to their portfolio decisions during such abnormal market times. Originality : The USA, Europe, and China have been the main subjects of market timing studies. Few studies on Australian finances were conducted during the pandemic, according to the literature assessment. We found that when markets are extremely turbulent, fund managers churn their portfolios and demonstrate greater capabilities. This information would be useful to both domestic and international investors.